Lina Bo Bardi, Brasil (1992)
Centro de Lazer SESC "Fábrica da Pompéia", Sao Paulo, Brasil, 1981-89.
Keywords: BO BARDI, LINA; BRASIL; SAN PABLO; REFUNCIONALIZACION ARQUITECTONICA; CENTROS COMUNITARIOS; CENTROS DEPORTIVOS; HORMIGON ARMADO